An investigation into accelerated leaching for the purpose of ARD mitigation - Opitz, Alexander Karl Benjamin (Centre for Bioprocess Engineering Research, 2015)
World-wide, acid rock drainage (ARD) is one of the biggest environmental challenges facing environments with current or previously active mining activities. Formed from the exposure of sulphide mineral to both water and air, and catalyzed by naturally occurring iron- and sulphur-oxidizing micro-organisms, ARD pollution is predominantly associated with the mining of sulphidic ores and coal. Of particular concern are the large volumes of mining wastes from which the generation of ARD and the associated pollution effects often persist over tens to hundreds of years after mining operations have ceased. Current ARD management strategies focus on the prevention of ARD through mineral waste deposition or remediation options once ARD has formed. These strategies, however, do not remove the risk of ARD generation in the future. The aim of this study was to investigate the removal of the potential for ARD generation from a low-grade copper waste rock through the accelerated removal of the sulphur components via reaction. The three waste rock samples used in this investigation had total sulphur grades of between 2.20 and 3.20 % with the majority of the sulphide present as pyrite, chalcopyrite and galena. Significant quantities of non-sulphide associated iron minerals, predominantly magnetite, were also present in the three samples. The waste rock samples were sourced from mining operations in Chile and South Africa and had a D80 of approximately 0.8 cm. All three waste rock samples were potentially ARD generating.